HUBUNGAN KECANDUAN GAME ONLINE MOBILE LEGENDS: BANG BANG (MLBB) DENGAN AGRESI VERBAL PADA MAHASISWA - Iffah Afiifah Sumayyah Ataana; Rahayu Hardianti Utami (Jurnal Riset Psikologi, 2025)
his study aims to investigate the levels of game addiction and verbal aggression among college students, as well as to explore the relationship between these two factors. Utilizing a quantitative correlational research design, the study focused on a population of 284 students who are reported to be addicted to the MLBB  game. The sampling technique employed was purposive sampling to ensure a targeted selection of participants. Data collection involved the use of a game addiction scale and a verbal aggression scale to gauge the participants' experiences. The analysis of the data was performed using the Spearman Rho correlation method. The results of the research are addicted to the MLBB  game in students is in the high category and verbal aggression in students who play MLBB  games is in the medium category. Then a significant positive relationship was found between addiction to the MLBB  game with verbal aggression in college students with a significance value of 0.000 <0.005 with a relationship strength of 0.307. Which means the higher the addiction to the online game MLBB  game in college students, the higher the verbal aggression they show, although the strength of the relationship is still at a weak level. The implications of these findings indicate the importance of managing the duration of playing online games in college students to prevent negative impacts such as verbal aggression. These results can also serve as a reference for educational institutions in designing educational programs that support the development of communication skills and emotion regulation. In addition, this study opens room for further studies by considering other variables that could potentially moderate the relationship between gaming addiction and verbal aggression.